2018
DOI: 10.1371/journal.pone.0208988
|View full text |Cite
|
Sign up to set email alerts
|

Interdependences between finger movement direction and haptic perception of oriented textures

Abstract: Although the natural haptic perception of textures includes active finger movements, it is unclear how closely perception and movements are linked. Here we investigated this question using oriented textures. Textures that are composed of periodically repeating grooves have a clear orientation defined by the grooves. The direction of finger movement relative to texture orientation determines the availability of temporal cues to the spatial period of the texture. These cues are absent during movements directed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 61 publications
2
22
0
Order By: Relevance
“…We did so under relatively well-defined conditions (e.g., of exploration). This perspective had been proven fruitful in previous studies (Lezkan & Drewing, 2018a , 2018b ; Metzger et al, 2018 ). It also allowed us to simplify the description of the exploratory movement and information gathering by its discretization into successive stroke units.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…We did so under relatively well-defined conditions (e.g., of exploration). This perspective had been proven fruitful in previous studies (Lezkan & Drewing, 2018a , 2018b ; Metzger et al, 2018 ). It also allowed us to simplify the description of the exploratory movement and information gathering by its discretization into successive stroke units.…”
Section: Introductionmentioning
confidence: 82%
“…A haptic sensory memory would be an appropriate mechanism to preserve and integrate redundant haptic information gathered during the exploration of a stimulus. Sensory memories are involved in information integration in the range of a few seconds, which covers observed durations of the haptic exploration of single stimuli (Lezkan et al, 2018 ; Lezkan & Drewing, 2018a ). One characteristic of sensory memories is that masking interferes with its integration capabilities, erasing or perturbing the content of the sensory memory (Averbach & Sperling, 1961 ; Gegenfurtner & Sperling, 1993 ).…”
Section: Introductionmentioning
confidence: 99%
“…With adaptive active sensing it is expected that scanning velocities are tuned to optimize receptor activation. It has been shown that primates prefer hand movement patterns that preserve certain temporal cues (Cascio & Sathian, 2001;Drewing, 2012;Gamzu & Ahissar, 2001;Hollins & Risner, 2000;Lezkan & Drewing, 2018), cues whose temporal frequencies best fit one class of mechanoreceptors in the fingertip (Abraira & Ginty, 2013;Ahissar, 1998;Johansson et al, 1982;Talbot et al, 1968) .Hence, adaptive active sensing predicts that variations in hand speeds across participants should correspond to variations in the spatial spacing of their receptors. In this case, the temporal frequencies of activation will be preserved in the preferred working range, as the temporal frequency generated on the skin when scanning a single edge is determined by the multiplication of the finger speed and the spatial frequency of receptors across the skin (Darian- Smith & Oke, 1980).…”
Section: Palpation Speed Correlates With the Participant's Spatial Rementioning
confidence: 99%
“…CF variants were further analyzed in consequent studies (Klatzky & Balakrishnan, 1991;Lederman & Balakrishnan, 1991;reviewed in Nelinger et al, 2015). Quantitative studies of planar (2D) objects revealed that humans adapt their movement patterns to the spatial characteristics of the scanned surfaces; speed, for example, is adapted to spatial frequency (Gamzu & Ahissar, 2001) and direction -to the spatial orientation of the surface's texture (Drewing, 2012;Lezkan & Drewing, 2018). Such adaptations evolve through development (Withagen et al, 2013), can be acquired via consequent exposures to specific features (Lezkan & Drewing, 2018;Withagen et al, 2013) and can be directly taught (Gamzu & Ahissar, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation